From DNA to catalysis: a thymine-acetate ligated non-heme iron(iii) catalyst for oxidative activation of aliphatic C–H bonds. Issue 10 (21st December 2015) - Al-hunaiti, Afnan; Räisänen, Minnä; Repo, Timo
Abstract : A non-heme, iron(iii )/THA(thymine-1-acetate) catalyst together with H2 O2 as an oxidant is efficient in oxidative C–H activation of alkanes. Abstract : A non-heme, iron(iii )/THA(thymine-1-acetate) catalyst together with H2 O2 as an oxidant is efficient in oxidative C–H activation of alkanes. Although having a higher preference for tertiary C–H bonds, the catalyst also oxidizes aliphatic secondary C–H bonds into carbonyl compounds with good to excellent conversions. Based on the site selectivity of the catalyst and our mechanistic studies the reaction proceeds via an Fe-oxo species without long lived carbon centered radicals.